Systems analysis and design methods - Whitten, Jeffrey L. (Irwin/McGraw-Hill, 2001)
Today's students want to practice the application of concepts. As with the previous editions of this book, the authors write to balance the coverage of concepts, tools, techniques, and their applications, and to provide the most examples of system analysis and design deliverables available in any book. The textbook also serves the reader as a professional reference for best current practices.